Geometry from coastal life: A grounded theory of primary students’ 3D geometry understanding in Northern Coastal West Java - Endang Wahyuningrum; Sudirman Sudirman; Camilo Andrés Rodríguez-Nieto (CV. FOUNDAE, 2025)
Background: Although three-dimensional (3D) geometry is an essential component of the elementary school mathematics curriculum, research exploring how students develop spatial understanding of 3D geometric objects in authentic learning contexts remains limited. Furthermore, the challenge of bridging visual, verbal, and manipulative representations persists as a major gap in the literature.Aims: This study aims to address this gap by examining the process through which elementary students develop conceptual understanding of 3D geometry using a grounded theory approach.Method: The study was conducted at a public elementary school in Indramayu Regency, West Java, Indonesia. A total of 26 students (20 female and 6 male, aged 11–12) voluntarily participated. Data were collected through 3D geometric visualization tests and in-depth interviews focusing on students' thought processes in imagining, comparing, and manipulating spatial forms. Data analysis followed the three stages of grounded theory methodology: open coding, axial coding, and selective coding, to construct a theory grounded in empirical data.Results: The findings reveal that students’ understanding of 3D volume is still in a transitional stage, moving from concrete experiences to formal mathematical representations. Familiar local contexts alone were found insufficient to bridge spatial understanding without adequate visual and pedagogical support. Major obstacles included conceptual misconceptions, procedural errors, limited visualization skills, and reliance on teacher assistance.Conclusion: The core category, “multiple representations as a bridge to spatial understanding,” underscores the importance of integrating concrete visualization, verbal description, and mathematical symbolism in geometry instruction. This study suggests that teachers should design instructional strategies that systematically combine visual media, concrete manipulatives, and verbal approaches. Such integration is crucial to ensure that local contexts effectively serve as a bridge between real-world experiences and abstract mathematical understanding.